2019
DOI: 10.1111/joss.12501
|View full text |Cite
|
Sign up to set email alerts
|

Natural: A $75 billion word with no definition—Why not?

Abstract: Natural is a $75 billion word with no official definition in most countries. The United States Food and Drug Administration has given only an unclear guideline on what constitutes natural instead of an actual definition. Sensory and other scientists need to understand the motivations and attitudes of consumers about the products they use. “Natural” is a commonly used term on labels and advertising for food and other products. This research examined 30 ingredients used in food products to determine which ingred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…At the same time consumers want products made from natural ingredients and Chambers, Chambers IV, and Castro (2018) found that insect powder was considered natural by only 7% of the US population in their survey. Further research (Chambers, Tran, & Chambers IV, 2019) found that US consumers either did not know what "Cricket Powder" was or found it disgusting.…”
mentioning
confidence: 99%
“…At the same time consumers want products made from natural ingredients and Chambers, Chambers IV, and Castro (2018) found that insect powder was considered natural by only 7% of the US population in their survey. Further research (Chambers, Tran, & Chambers IV, 2019) found that US consumers either did not know what "Cricket Powder" was or found it disgusting.…”
mentioning
confidence: 99%
“…Those authors suggested just such a scenario based on their findings that unfamiliarity with such products was a major negative factor in eating insect‐based products. Chambers, Tran, and Chambers (2019) and Chambers, Chambers, and Castro (2018) noted that having unfamiliar ingredients in products implied to consumers that the products were not natural. Chambers et al.…”
Section: Resultsmentioning
confidence: 99%
“…Chambers et al. (2019) specifically found in the United States of America that cricket powder was both unfamiliar (>50% of consumers) and was considered disgusting (∼10%).…”
Section: Resultsmentioning
confidence: 99%
“…The multidimensionality of the importance of naturalness for consumers has been discussed by a number of scholars, who have identified a wide range of attributes used for measuring this concept [6,8,13,[32][33][34][35][36][37], leading to a lack of consensus about its definition [6].…”
Section: Food Naturalness and Millennials' Behaviormentioning
confidence: 99%
“…It cannot be disregarded that present and future tendencies of food consumption are specified by what millennials value the most [1][2][3][4][5]. The importance of food naturalness for consumers and its impact on their behavior has been widely studied in the literature (e.g., [6][7][8][9]). Among others, previous studies have suggested attributes such as the absence of additives and the presence of natural ingredients [10,11], being unprocessed [12], or containing organically grown products [13].…”
Section: Introductionmentioning
confidence: 99%